Dynamic Susceptibility Contrast-Enhanced Perfusion and Conventional MR Imaging Findings for Adult Patients with Cerebral Primitive Neuroectodermal Tumors - Law, Meng; Kazmi, Khuram; Wetzel, Stephan; Wang, Edwin; Iacob, Codrin; Zagzag, David; Golfinos, John G.; Johnson, Glyn (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Preoperative differentiation of primitive neuroectodermal tumors (PNETs) from other tumors is important for presurgical staging, intraoperative management, and postoperative treatment. Dynamic, susceptibility-weighted, contrast-enhanced MR imaging can provide in vivo assessment of the microvasculature in intracranial mass lesions. The purpose of this study was to determine the perfusion characteristics of adult cerebral PNETs and to compare those values with low and high grade gliomas.METHODS: Conventional MR images of 12 adult patients with pathologically proved cerebral PNETs were analyzed and provided a preoperative diagnosis. Relative cerebral blood volume (rCBV) measurements and estimates of the vascular permeability transfer constant, Ktrans, derived by a pharmacokinetic modeling algorithm, were also obtained. These results were compared with rCBV and Ktrans values obtained in a group of low grade gliomas (n = 30) and a group of high grade gliomas (n = 55) by using a Student t test.RESULTS: On conventional MR images, PNETs were generally well-defined contrast-enhancing masses with solid and cystic components, little or no surrounding edema, and occasional regions of susceptibility. The rCBV of cerebral PNETs was 4.76 ± 1.99 SD, and the Ktrans was 0.0033 ± 0.0035. A comparative group of patients with low grade gliomas (n = 30) had significantly lower rCBV (P < .0005) and lower Ktrans (P < .05). Comparison with a group of high grade gliomas showed no statistical significance in the rCBV and Ktrans (P = .53 and .19, respectively).CONCLUSION: Dynamic, susceptibility-weighted, contrast-enhanced MR imaging shows areas of increased cerebral blood volume and vascular permeability in PNETs. These results may be helpful in the diagnosis and preoperative differentiation between PNETs and other intracranial mass lesions (such as low grade gliomas), which have decreased perfusion but may sometimes have a similar conventional MR imaging appearance.